Village Fund Management: Identifying Challenges and Strategic Solutions - Idrus, Nur Azizah Afifah; Haliah, Haliah; Kusumawati, Andi (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
Village fund management become material conversation a number of year lately this. Village fund management cause various problems and challenges. Research this aiming for identify problem or challenge in village fund management and formulating effective solution so that created welfare for public village. This article based on the approach qualitative with analysis studies literature. Focus his research is identify challenge village fund management from various reference related. This article has succeed identify challenge in village fund management and proposals the right solution for effective and efficient management of village funds to realize welfare public village. This article recommend for each other synergy with all related parties for economy prosperous village.